Hydrological Analysis In Selecting Flood Discharge Method In Watershed Of Kelara River - Mustamin, Muhammad Rifaldi; Maricar, Farouk; Karamma, Riswal (INTEK: Jurnal Penelitian, 2021)
For Engineers involved in planning and construction of water resources building, hydrology becomes very important data. In terms of planning stage in water resources especially waterworks, it is known that design flood discharge closed to field realistic conditions is often needed in order that a planned construction is able to control flood discharge. Several previous researches in choosing flood discharge selection method have diverse depending on observed watershed. One method in determining selected flood discharge by verification using Creager diagram, by comparing discharge calculation results of several Synthetic Unit Hydrograph (SUH) with infrastructure flood discharge (AWLR result) in observation point. This research aims to obtain the most suitable synthetic unit hydrograph and close to analysis result of measured discharge frequency, and Creager diagram in Kelara watershed (DAS). Based on the calculation of design flood discharge according to rainfall data using synthetic unit hydrograph of Nakayasu, ITB I, ITB II, and SCS (HEC-HMS) as well as the calculation of design flood discharge according to collected data, it is concluded that the synthetic unit hydrograph method closest to design flood discharge with measured discharge rate and Q1000 rate of Creager diagram is SCS. Flood discharge rate obtained according to HSS SCS method using HEC-HMS 4.8 application in period of 2 years is 658,40 m3/s, 25 years is 682,70 m3/s, 50 years is 787,00 m3/s, 100 years is 885,70 m3/det, and 1000 years is 1202,60 m3/s